PROFIL HEMATOLOGI CACING NIPAH (Namalycastis rhodochorde) DI MUARA SUNGAI KAKAP KABUPATEN KUBU RAYA, KALIMANTAN BARAT - Ramadani, Ririn (Universitas Tribhuwana Tunggadewi, 2023)
Physiological data on Nypa palm worm hemocytes can be used as a standard reference for healthy Nypa palm worms and the basis for preventive measures and treatment of diseases in cultivation activities because hemocytes have an important function in regulating the physiology of the body. The hematological profile of the Nypa palm worm (Namalycastis rhodochorde) includes total hemocytes, hemocyte diameter, hemoglobin, and blood viscosity. The research was conducted to determine the hematological condition of nypa palm worms. The study used the calculation room method in the examination of total hemocytes, the manufacture of smear preparations looked at the appearance of hemocyte morphology, and the use of the Sahli thermometer device for hemoglobin examination and viscometer for viscosity examination. The results showed that the average number of total hemocytes of Nypa palm worms was 1.79 x106 cells / L the diameter of hemocytes had an average of 5.17μm, hemoglobin had an average value of 5.60 g / dl, and an average viscosity measurement of 3.25 N.s / m3. The hemocyte profile of the Nypa palm worm shows its correlation, the total number of hemocytes, hemoglobin, and blood viscosity of the Nypa palm worm. However, there is no relationship between the size of the diameter of the blood hemocytes of the Nypa palm worm and the parameters of the total number of hemocytes, hemoglobin, and blood viscosity.